Self-esteem and addictive smartphone use: The mediator role of anxiety and the moderator role of self-control. (May 2021) - Gao, Qiufeng; Fu, En; Xiang, Yanhui; Jia, Ge; Wu, Shiyi
Highlights: Anxiety mediates the association between self-esteem and addictive smartphone use. Self-esteem is negatively associated with anxiety. Anxiety is positively associated with addictive smartphone use. Self-control moderates the association between self-esteem and anxiety. Abstract: Background: Existing research supports an association between self-esteem and addictive smartphone use, yet the underlying mechanism is not clear. Building on the compensatory internet use model, the current study explored the possible mediator role of anxiety and moderator role of self-control in the link between self-esteem and addictive smartphone use. Method: Two middle schools and two elementary schools in a metropolitan city in China were selected through convenient sampling. Eleven hundred and twelve adolescents from those schools completed a paper-and-pencil survey, which included measurements of self-esteem, addictive smartphone use, anxiety, and self-control. The relationships among variables were analyzed using a moderated mediation model in an SPSS macro named PROCESS. Results: The moderated mediation model achieved satisfactory effect size, R 2  = 28.65%; Specifically, (1) anxiety fully mediated the association between self-esteem and addictive smartphone use, CI = [−0.1, −0.05]: Self-esteem was negatively related to anxiety, which in turn was positively related to addictive smartphone use; (2) moderated mediation analysis results showed that high self-control enhanced the protective effect of self-esteem against anxiety. Conclusions: High self-esteem in adolescents is related to relatively low anxiety, which is related to less addictive smartphone use. Moreover, the protective effect of self-esteem against anxiety was enhanced by high self-control, suggesting that increasing self-esteem alone would not prevent addictive smartphone use in all adolescents.